PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN METODE PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 - Benny Sofyan Samosir; Wiwik Novitasari; Masdelima Azizah Sormin; Yasril Efendi Hamdy Siregar; Lisna Agustina; Syahruddin Aritonang (Universitas Muhammadiyah Semarang, 2023)
This study aims to determine learning outcomes using the Google Classroom and Webinar Zoom platformsduring the Covid-19 pandemic. The type of research used is experimental research. The results of this study indicate that the average pretest value of the experimental class is 18.75 and the average value of the pretest experimental class 2 is 17.50, while the posttest average value of the experimental class 1 is 40.83 and the posttest average value experimental class 2 that is equal to 48.75. Furthermore, from the results of the independent sample t-test in the equal variances assumed section, it is known that the t-count value is -1.331, which means the average value in the experimental class 1 is lower than the average value of the experimental class 2, this indicates that there are differences in learning outcomes. mathematics students who use the Google Classroom and Webinar Zoom platforms during the Covid-19 pandemic for class XI IPA students at SMA Negeri 6 Padangsidimpuan.